Sonochemical approach for the synthesis of safflower oil based low fat emulsion: Effect of ultrasonic parameters. (2022) - Potdar, Shital; Bagale, Uday; Potoroko, Irina; Hakke, Vikas S.; Maralla, Yadagiri; Sivakumar, Manickam; Sonawane, Shirish
Abstract: In the present work, sonication parameters are investigated for the development of stable low-fat emulsion for food additive applications. The oil in water emulsions was synthesized by using safflower oil (SO) blended with milk powder and gum arabic in water. The effect of ultrasonic parameters such as probe tip diameter (10 mm, and 20 mm) and sonication time (5 min, 10 min, 20 min, and 30 min) on the particle size distribution and viscosity of an emulsion was observed. The rheological study of emulsion confirms the shear thinning behavior, indicates the achievement of uniform droplet distribution of SO in aqueous suspension. The morphology of the prepared emulsions was examined by field emission scanning electron microscope (FESEM) and transmission electron microscope (TEM) analysis. Droplet sizes of prepared emulsions were found to be in the range of 250–300 nm with narrow particle size distribution. The antimicrobial study reveals that the diameter of the bacterial inhibition zone remains constant to 7–8 mm indicating an antimicrobial characteristic of an emulsion. Antioxidant activities assessed with DPPH assay shows 45 ± 2.1% oxidation inhibition. The present observations will be the value additions in the synthesis of stable emulsions with optimal operating conditions.